GAMBARAN BEBERAPA FAKTOR KEJADIAN KARIES GIGI PADA SISWA TUNAGRAHITA DI SLB C, KOTA SEMARANG - Diajeng Sri Andriani Permatasari; Henry Setyawan Susanto; Ari Udiyono; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Caries is a disease of dental hard tissue, email, dentin and cementum, which is caused by the activity of a microorganism in a carbohydrate that can be fermented. Children with intellectual development disorders have a below average intellegence. The prevalence of caries in Indonesian children aged 12 years is 98%. The purpose of this study is to describe factor of dental caries in caries in students with intellectual development disorder in SLB C, Semarang. The population of this study are 123 students.The samples are part of the population who have the inclusion criteria. This research uses descriptive method with cross-sectional design. The results showed 66.3% of respondents are male, 83.2% of children with intellectual development disorders have dental caries, Average DMF-T index is 3.94 which according to WHO criteria in middle category, 44.6% of respondents have a relatively acidic pH of saliva, 52.5% higher cariogenic consumption, 16.8% of respondents oral hygiene medium category, 80.2% income parents than average, 53.5% of women respondents have good knowledge, 4% of respondents have a bad plaque, and 61.4% practice toothbrush is a good category.